The Dark Energy Survey Supernova Program results: type Ia supernova brightness correlates with host galaxy dust. Issue 2 (26th October 2022) - Meldorf, C; Palmese, A; Brout, D; Chen, R; Scolnic, D; Kelsey, L; Galbany, L; Hartley, W G; Davis, T M; Drlica-Wagner, A; Vincenzi, M; Annis, J; et al.
ABSTRACT: Cosmological analyses with type Ia supernovae (SNe Ia) often assume a single empirical relation between colour and luminosity (β) and do not account for varying host-galaxy dust properties. However, from studies of dust in large samples of galaxies, it is known that dust attenuation can vary significantly. Here, we take advantage of state-of-the-art modelling of galaxy properties to characterize dust parameters (dust attenuation AV, and a parameter describing the dust law slope RV ) for 1100 Dark Energy Survey (DES) SN host galaxies. Utilizing optical and infrared data of the hosts alone, we find three key aspects of host dust that impact SN cosmology: (1) there exists a large range (∼1–6) of host RV ; (2) high-stellar mass hosts have RV on average ∼0.7 lower than that of low-mass hosts; (3) for a subsample of 81 spectroscopically classified SNe there is a significant (>3σ) correlation between the Hubble diagram residuals of red SNe Ia and the host RV that when corrected for reduces scatter by $\sim 13{{\ \rm per\ cent}}$ and the significance of the 'mass step' to ∼1σ. These represent independent confirmations of recent predictions based on dust that attempted to explain the puzzling 'mass step' and intrinsic scatter (σint ) in SN Ia analyses.